Wheat Line “RYNO3936” Is Associated With Delayed Water Stress-Induced Leaf Senescence and Rapid Water-Deficit Stress Recovery - le Roux, Marlon-Schylor L.; Burger, N. Francois V.; Vlok, Maré; Kunert, Karl J.; Cullis, Christopher A.; Botha, Anna-Maria (Frontiers in Plant Science, 2020)
Random mutagenesis was applied to produce a new wheat mutant (RYNO3926) with superior characteristics regarding tolerance to water deficit treatment and rapid recovery from water stress conditions. Under water stress conditions mutant plants reached maturity faster and produced more seeds than its wild type wheat progenitor Further, whereas wild-type Tugela DN plants died within 7 days after induction of water stress, mutant plants survived by maintaining a higher relative moisture content (RMC), increased total chlorophyll, a higher photosynthesis rate and stomatal conductance. Analysis of the proteome of mutant plants revealed that they better regulate post-translational modification (SUMOylation) and have increased expression of ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCO) proteins. Mutant plants also expressed unique proteins associated with dehydration tolerance including abscisic stress-ripening protein, cold induced protein, cold-responsive protein, dehydrin, Group 3 late embryogenesis and also a lipoprotein (LAlv9) belonging to the family of lipocalins. Overall, our results suggest that our new mutant RYNO3936 has a potential for inclusion in future breeding programs to improve drought tolerance under dryland conditions.